Pre‐operative lymphocyte‐to‐monocyte ratio as a predictor of overall survival in patients suffering from osteosarcoma. Issue 1 (7th August 2015) - Liu, Tao; Fang, Xuan-Cheng; Ding, Zhen; Sun, Ze-Gan; Sun, Li-Ming; Wang, Yi-Lian
Abstract : Inflammatory markers have been proposed to predict clinical outcomes in many types of cancers. The purpose of this study was to explore the influence of the lymphocyte‐to‐monocyte ratio (LMR) on clinical prognosis of patients with osteosarcoma. This study collected 327 patients who underwent surgical treatment for osteosarcoma during the period 2006–2010. LMR was calculated from pre‐operative peripheral blood cells counts. The optimal cut‐off value of LMR was determined based on receiver operating characteristic curve analysis. Overall survival (OS) and event free survival (EFS) was plotted using the Kaplan–Meier method and evaluated by the log‐rank test. A predictive model was established to predict clinical prognosis for OS, and the predictive accuracy of this model was determined by concordance index ( c ‐index). Our results showed that young age, elevated alkaline phosphatase, metastasis at diagnosis, chemotherapy, lymphocyte and monocyte counts were significantly associated with LMR. Low LMR was associated with shorter OS and EFS ( P < 0.001), and was an independent predictor of both OS and EFS (HR = 1.72, 95% CI = 1.14–2.60, P = 0.010; HR = 1.89, 95% CI = 1.32–2.57, P = 0.009). The nomogram performed well in the prediction of overall survival in patients with osteosarcoma ( c ‐index 0.630). In conclusion, low pre‐operative LMR is associated with a poor prognosis in patients suffering from osteosarcoma. A prospective study is warranted for further validation of our results. Abstract : The influence of lymphocyte‐to monocyte ratio (LMR) on the clinical prognosis of osteosarcoma patients was explored. The study included 327 patients undergoing surgical treatment for osteosarcoma. LMR was calculated from pre‐operative peripheral blood cells counts. A predictive model was established to predict clinical prognosis for overall survival. Low pre‐operative LMR was associated with a poor prognosis in osteosarcoma patients.